High-dose immunosuppressive therapy and autologous HCT for relapsing-remitting MS. (28th February 2017) - Nash, Richard A.; Hutton, George J.; Racke, Michael K.; Popat, Uday; Devine, Steven M.; Steinmiller, Kaitlyn C.; Griffith, Linda M.; Muraro, Paolo A.; Openshaw, Harry; Sayre, Peter H.; Stuve, Olaf; Arnold, Douglas L.; et al.
Abstract : Objective: To evaluate the safety, efficacy, and durability of multiple sclerosis (MS) disease stabilization after high-dose immunosuppressive therapy (HDIT) and autologous hematopoietic cell transplantation (HCT). Methods: High-Dose Immunosuppression and Autologous Transplantation for Multiple Sclerosis (HALT-MS) is a phase II clinical trial of HDIT/HCT for patients with relapsing-remitting (RR) MS who experienced relapses with disability progression (Expanded Disability Status Scale [EDSS] 3.0–5.5) while on MS disease-modifying therapy. The primary endpoint was event-free survival (EFS), defined as survival without death or disease activity from any one of: disability progression, relapse, or new lesions on MRI. Participants were evaluated through 5 years posttransplant. Toxicities were reported using the National Cancer Institute Common Terminology Criteria for Adverse Events (AE). Results: Twenty-five participants were evaluated for transplant and 24 participants underwent HDIT/HCT. Median follow-up was 62 months (range 12–72). EFS was 69.2% (90% confidence interval [CI] 50.2–82.1). Progression-free survival, clinical relapse-free survival, and MRI activity-free survival were 91.3% (90% CI 74.7%–97.2%), 86.9% (90% CI 69.5%–94.7%), and 86.3% (90% CI 68.1%–94.5%), respectively. AE due to HDIT/HCT were consistent with expected toxicities and there were no significant late neurologic adverse effects noted. Improvements were noted in neurologic disability with a median change in EDSS of −0.5 (interquartile range −1.5 to 0.0; p = 0.001) among participants who survived and completed the study. Conclusion: HDIT/HCT without maintenance therapy was effective for inducing long-term sustained remissions of active RRMS at 5 years. ClinicalTrials.gov identifier: NCT00288626. Classification of evidence: This study provides Class IV evidence that participants with RRMS experienced sustained remissions with toxicities as expected from HDIT/HCT.